An E3 ubiquitin ligase TRIM9 is involved in WSSV infection via interaction with β-TrCP. (August 2019) - Sun, Mingzhe; Li, Shihao; Yu, Kuijie; Xiang, Jianhai; Li, Fuhua
Abstract: The TRIpartite Motif (TRIM) proteins are known to play key roles in cell differentiation, apoptosis, development, autophagy and innate immunity. In the present study, a TRIM9 homolog (named Lv TRIM9) was identified from the transcriptome of the Pacific whiteleg shrimp Litopenaeus vannamei . The deduced amino acid sequence of Lv TRIM9 possessed typical features of TRIMs, consisting of a RING domain, two B-boxes, a coiled-coil domain, a FN3 domain, and a SPRY domain. The transcript of Lv TRIM9 was detected in most tissues of the shrimp. Its expression level was obviously up-regulated at 3, 12 and 24 h post white spot syndrome virus (WSSV) infection. Knockdown of Lv TRIM9 gene expression by double-strand RNA mediated interference could lead to a decrease of virus copy number in WSSV-infected shrimp. Yeast two-hybrid analysis showed that Lv TRIM9 could directly interact with beta-transducin repeat-containing protein of shrimp ( Lv β-TrCP), an inhibitor of NF-κB pathway. Meanwhile, knockdown of Lv TRIM9 could also up-regulate the expression levels of Lv Relish and downstream production of antimicrobial peptides in the intestine of shrimp. These data indicated that WSSV might hijack the Lv TRIM9 for its propagation through inhibition of NF-κB pathway and downstream antimicrobial peptides production via interaction of Lv TRIM9 with Lv β-TrCP in shrimp. The study improved our understanding about the impact of E3 ubiquitin ligases on the innate immune signaling pathway of shrimp and its role during WSSV infection. Highlights: WSSV infection up-regulated the expression level of Lv TRIM9. Silencing of Lv TRIM9 reduced virus replication in WSSV infected shrimp. Lv TRIM9 could directly interact with Lv β-TrCP. Silencing of Lv TRIM9 up-regulated the expression levels of Lv Relish and AMPs.